TRENDS IN INCREASING CASES OF MENTAL DISORDERS IN ADOLESCENTS: A CASE STUDY IN PONOROGO REGENCY - Niswa Asmi Zameilani; Asmahan Luthfi Rahmadani; Nur Muhammad; Andhita Risko Faristiana; Dony Rano Virdaus (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to understand the patterns causing an increase in mental disorders among adolescents in Ponorogo Regency, as well as to identify the contributing factors and appropriate treatment strategies in the local socio-cultural context. The background of this study is based on the increasing number of cases of mental disorders among adolescents in East Java, including Ponorogo, as recorded in the 2022 Riskesdas (Basic Health Research) that 5.5% of Indonesian adolescents experience mental health problems. The study used a qualitative method with a case study design in Danyang Hamlet and Paringan Village. Data was obtained through in-depth interviews, observations, and documentation of families of adolescents with mental disorders, community leaders, and managers of the Margo Widodo Mental Health Therapy Centre. The results of the study show that the emergence of mental disorders in adolescents follows a pattern that begins with mild psychological symptoms, which are exacerbated by emotional pressure, family conflicts, economic problems, and bullying in school or boarding school environments. An unsupportive social environment exacerbates the condition, leading to severe disorders and even suicide. The study concludes that the increase in mental disorders cases among adolescents is influenced by a combination of personal vulnerability and environmental pressures, so effective prevention needs to be based on the family, strengthening emotional literacy, providing alternative activities, and support from others.